Міжнародна конкуренція регіонів – економічне явище глобалізації - Кутняк, О.В. (Культура народов Причерноморья, 2013)
Проаналізовано основні підходи до оцінки ролі регіонів у конкурентних процесах та
визначення сутності поняття “міжнародна конкуренція регіонів”. З метою уточнення сутності
міжнародної конкуренції регіонів ідентифіковано основні елементи даного поняття. Представлено
авторське тлумачення міжнародної конкуренції регіонів, яке відрізняється від існуючих визначень
системним характером та акцентуванням уваги на структурних змінах, що відбуваються у світовій
економіці. Визначено основні ознаки міжнародної конкуренції регіонів як економічного явища
глобалізації. Проанализированы основные подходы к оценке роли регионов в конкурентных процессах и
определению сущности понятия “международная конкуренция регионов”. С целью уточнения сущности
международной конкуренции регионов идентифицированы основные элементы данного понятия.
Представлено авторское толкование международной конкуренции регионов, которое отличается от
существующих определений системным характером и акцентированием внимания на структурных
изменениях, которые происходят в мировой экономике. Определены основные признаки международной
конкуренции регионов как экономического явления глобализации. Two opposite approaches to the estimation of the regions’ role in competitive processes are analyzed,
the tendency to transformation of regions into independent participants of world competitive processes is
focused on. The main approaches to the essence of the term “international competition of regions” are
determined. The basic elements of the term “international competition of regions” as for instance
competitiveness, cause, factor, competition, effect, purpose and development are identified to specify the essence
of the term. The author’s interpretation of the international competition of regions is represented, it is
determined as the process, caused by conflict of unilateral interests of regions and aimed at economic and social
regional development and strengthening the region’s competitive position in the world economic space. The
main features of the international competition of regions as economic phenomenon of the globalization are
determined, they are: emergence and functioning in an integrated world space, large scale; intensification of the
competition between regions; change of the end-points from a profit to the scale of the liquid resources’ release;
displacement of the competitive advantages to development of innovation-technological, informational,
intellectual potential; presence of the destructive component of the international competition of regions.